Unit’s Heterogeneity and System Differentiation: The Logic of U.S.-China Relations’ Transition - Tu, Minghui (Journal of Advanced Research in Social Sciences, 2022)
In this paper, Unit Heterogeneity and the Degree of system differentiation are considered as the independent variables to explain the differential characteristics of the international structure, which lead to a differentiated interaction mode between hegemon and other rising powers. Then the paper further argues that globalization and nuclear deterrence lead to dynamic changes in system differentiation, and the heterogeneity between rising power and hegemonic power in geographical objectives, strategic culture, ideology, and polity are the conditions that hegemon must refer to when positioning the nature of rising power and interacting with rising power. However, the logic of power distribution is implied in the degree of system differentiation, and the author finds that in the process of globalization promoted by the hegemon if the relative power of rising powers becomes unconstrained, the hegemon will slow down globalization and suppress rising powers instead. The degree of urgency relates not only to power distribution but also to unit heterogeneity. Therefore, the paper distinguished four patterns in terms of great powers’ competition: duopoly competition in orderly anarchy status, alliance management in rigid hierarchy status, the dual-track embedded competition in loose hierarchy status, and quasi-perfect competition in chaotic anarchy status. In the end, the article verified the common modes of great power interaction, which are reflected in the competition between the U.S. and the USSR, differing interests between hegemon and allies inside the hegemon alliance, and U.S.-China competition.